Posted by **tish** on Monday, April 25, 2011 at 11:46am.

(12x + 5t)-(14t-6x)

12x + 5t - 14t -6x ( I get lost here when the -6x changes to +6.

Same as this question:

(5x + 2z)-(2x - 11z)

Can anyone explain this to me? Thank you

## Answer this Question

## Related Questions

- Calculus - Consider the parametric curve given by the equations x(t)=t^2–14t–4 y...
- Math - The population size, P, of owls (predators) in a certain region can be ...
- algebra - 24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3...
- algebra - 5x -3 = 11 + 12x combine like figures add 3 to both sides to remove ...
- algebra2 - 1/3 - 5/6 = 1/X SOLVE 1/3 - 5/6 = 1/X Let's remove the denominators ...
- calc - What is dy/dx of y=12/12X-y^3 ???? Any idea anyone??? y=12/12X-y^3 I ...
- Algebra - Can someone please check my work for me. Q: Plot the graph of the ...
- math - Please explain how to get the answer. At the animal shelter, 1/3 of the ...
- math - how do i do x2+12x+32 x2+12x = 14x+32 subtract 14x from each side 14x=32 ...
- Math Homework: Check Answers - 1. Suppose you earned 8t - 3 dollars on Monday ...